Photoluminescence of two-dimensional GaTe and GaSe films. (30th July 2015) - Pozo-Zamudio, O Del; Schwarz, S; Sich, M; Akimov, I A; Bayer, M; Schofield, R C; Chekhovich, E A; Robinson, B J; Kay, N D; Kolosov, O V; A I Dmitriev,; Lashkarev, G V; et al.
Abstract: Gallium chalcogenides are promising building blocks for novel van der Waals heterostructures. We report on the low-temperature micro-photoluminescence (PL) of GaTe and GaSe films with thicknesses ranging from 200 nm to a single unit cell. In both materials, PL shows a dramatic decrease by 10 4 –10 5 when film thickness is reduced from 200 to 10 nm. Based on evidence from continuous-wave (cw) and time-resolved PL, we propose a model explaining the PL decrease as a result of non-radiative carrier escape via surface states. Our results emphasize the need for special passivation of two-dimensional films for optoelectronic applications.